Perlindungan Hukum dengan Pemberian Restitusi terhadap Anak Sebagai Korban Tindak Pidana Pencabulan - Dilla Kartika Odje; Bhisa Vitus Wilhelmus; Deddy R. Ch. Manafe (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The crime of obscenity is still a problem that is very difficult to eliminate. The main target of criminal acts of molestation often occurs in minors. Criminal acts of abuse that occur can have long-term impacts on children as victims both physically, psychologically, and socially. The research method used by the author is normative legal research, by reviewing or examining laws and regulations and court decisions related to the legal issues at hand. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials which are then analyzed qualitatively descriptively. The results of this study show that: (1) The basis for the consideration of the Panel of Judges in imposing a sentence on the perpetrator of the crime of child abuse in the case of Decision Number 69/Pid.Sus/2023/PN Bajawa is to consider its juridical and non-juridical aspects. (2) Regarding the legal consequences if the Restitution is unable to be paid by the Defendant so far has not been specifically regulated either in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and Government Regulation Number 43 of 2017 concerning the Implementation of Restitution for Children Who Are Victims of Criminal Acts. If there is no provision that specifically regulates the penalty in lieu of restitution, there will be a small possibility for the Victim's Child to receive his rights.